Academic Culture and Students' Scientific Attitudes In Improving The Quality of Higher Education: Research at the Indonesian Institute of Education and Garut University - Dodi Misbah Jalaludin; Muhibbin Syah; Asep Nursobah; Andewi Suhartini (Jurnal Impresi Indonesia, 2024)
Building an academic culture is not an easy thing to do, it requires socialization and supervision of all ongoing academic activities, so that a habit is built among the academic community to obey and comply with the academic rules that have been set. The purpose of this study is the implementation of academic culture and scientific attitudes of students in order to improve the quality of higher education. This research uses a qualitative approach with descriptive methods. This research was conducted at the Indonesian Institute of Education (IPI) Garut and Garut University (UNIGA) as the research locus. By using a qualitative approach with descriptive methods. Data collection techniques using interview techniques, observation, and documentation. The stages of data analysis were carried out by reducing data, displaying data, and drawing conclusions. The results of this study indicate that the academic culture of students at IPI Garut includes a culture of literacy, research, seminars and publications. Then the scientific attitude of IPI Garut students can be seen from classroom discussions. The academic culture of students on the UNIGA campus includes seminars, workshops, publications, etc. The scientific attitude of UNIGA students includes critical thinking, curiosity, discussion, writing and other activities. However, all of these things have not been fully implemented properly.